A Selective Cucurbit[8]uril‐Peptide Beacon Ensemble for the Ratiometric Fluorescence Detection of Peptides. Issue 57 (17th September 2019) - Maity, Debabrata; Assaf, Khaleel I.; Sicking, Wilhelm; Hirschhäuser, Christoph; Nau, Werner M.; Schmuck, Carsten
Abstract: A convenient supramolecular strategy for constructing a ratiometric fluorescent chemosensing ensemble, consisting of a macrocyclic host (cucurbit[8]uril CB[8]), and a pyrene‐tagged amphiphilic peptide beacon (AP 1), is reported. AP 1 unfolds upon encapsulation of the pyrene termini into the hydrophobic CB[8] cavity. This changes pyrene excimer to monomer emission. Substrates with higher affinity for the CB[8] cavity can displace AP 1 from the ensemble. The released AP 1 folds again to form a pyrene excimer, which allows for the ratiometric fluorescence monitoring of the substrate. In this report, the ensemble capacity for ratiometric fluorescence monitoring of biological substrates, such as amino acid derivatives, specific peptides, and proteins, in aqueous media is demonstrated. Abstract : A switching chemosensing ensemble was obtained by combining a macrocyclic host, cucurbit[8]uril (CB[8]), and a pyrene‐tagged amphiphilic peptide beacon (AP 1) for excellent ratiometric fluorescent recognition of biological substrates in aqueous media. The pyrene termini of the flexible AP 1 compete with substrates for encapsulation into the CB[8] cavity which changes pyrene excimer/monomer emission.